Effects of rotation on transient fluid flow and heat transfer through a curved square duct: the case of negative rotation - Hasan, Mohammad Sanjeed; Mollah, Md. Tusher; Kumar, Dipankar; Mondal, Rabindra Nath; Lorenzini, Giulio (Zielona Góra: Uniwersytet Zielonogórski)
The fluid flow and heat transfer through a rotating curved duct has received much attention in recent years because of vast applications in mechanical devices. It is noticed that there occur two different types of rotations in a rotating curved duct such as positive and negative rotation. The positive rotation through the curved duct is widely investigated while the investigation on the negative rotation is rarely available.
Keywords: flow transition; temperature gradient; unsteady and vortex diagram; experimental validation